Theory and practice of modern antenna range measurements - Parini, Clive; Gregson, Stuart Fraser; McCormick, John (Lead radar systems engineer); Van Rensburg, Daniël Janse (IET electromagnetic waves series ;, 2014)
This volume provides a comprehensive introduction and explanation of both the theory and practice of all forms of modern antenna measurements, electromagnetic theory, antenna coupling, compact range measurements, near-field antenna measurements, mobile and body-centric antenna measurements.